Comparative Evaluation of Biomarkers of Inflammation Among Indian Women With Polycystic Ovary Syndrome (PCOS) Consuming Vegetarian vs. Non-vegetarian Diet - Ganie, Mohd Ashraf; Sahar, Tajali; Rashid, Aafia; Wani, Ishfaq A.; Nisar, Sobia; Sathyapalan, Thozhukat; Vishnubhatla, Sreenivas; Ramakrishnan, Lakshmy; Parvez, Tabasum; Geer, Ishaq (Frontiers in Endocrinology, 2019)
Background: Sub-inflammation and insulin resistance characterizes women with PCOS. Data on dietary modulation of inflammation among PCOS women is scant, particularly from Indian subcontinent. Methods: This observational case-control study enrolled women with PCOS diagnosed as per the Rotterdam 2003 criteria and apparently healthy, age and BMI matched women from two populations following different dietary practices (vegetarian from New-Delhi; n=82 PCOS and n=179 healthy and non-vegetarian from Srinagar; n=62 PCOS and n=141 healthy women). Using a uniform methodology, a detailed clinical, biochemical, hormonal and inflammatory marker assessment was undertaken. Results: The mean age of the overall cohort was 26.23±4.59years with a mean BMI of 24.39±3.72kg/m2. Overall pro-inflammatory markers (TNF-α, IL-6, IL-1β, hs-CRP and serum resistin) were significantly higher (p<0.05) and anti-inflammatory markers (IL-10 and adiponectin) were lower among women with PCOS than healthy subjects. On comparing vegetarian women with non-vegetarians counterparts, higher daily calorie intake (1895.46± 258.19 vs. 1860.13±323.96 Kcal) with a higher protein and fat and lower carbohydrate intake was recorded in the latter, although the percent energy derived from carbohydrates was higher among vegetarians. Clinical, biochemical and hormonal parameters were comparable among the groups except mFG score, total serum testosterone and serum lipid levels which were higher among non-vegetarian women as compared to their vegetarian counterparts from both categories (PCOS and healthy). Interestingly, vegetarian women with PCOS and healthy women had higher serum pro-inflammatory and lower anti-inflammatory markers compared to their non-vegetarian counterparts. Conclusion: We conclude that PCOS women consuming Indian vegetarian diet have higher pro-inflammatory and lower anti-inflammatory marker levels than their age and BMI matched healthy non-vegetarian counterparts. This interesting observation can be attributed to the dietary composition, among other factors and needs confirmation from well-designed randomized studies on a larger cohort. Clinical Trial Registration: The study was registered with CTRI database under registration number CTRI/2013/09/003996